من بلاغة الكلمة إلى بلاغة الصورة: مضمار التشكيل الجمالي للصورة الشعرية في القصيدة الجزائرية الجديدة. - عليوات, سامية (Université de Bouira; www. univ-bouira. dz, 2018)
يسعى هذا المقال إلى رصد آليات اشتغال الصورة الشعرية ومدارات تشكيلها في التصوّر الجديد لمفهومي الشّعر والصورة الشعرية، كما يبحث في مصادر الصّور ومدى تعبيرها عن الوضع العام الذي يحيا في كنفه الشعراء، وتعبيرها بشكل خاصّ عن الوضع النفسي والشعوري للشاعر، الذي يتوافق مع ما تعبّر عنه الرموز والأساطير التي شاع استخدامها بوصفها مصادر ثرية للتطابق بين الوضع الراهن وزمن تلك الرموز والأساطير. The use of words: the aesthetics of the poetic image in the contemporary Algerian poem. Abstract: This article strove to show the mechanisms of the functioning of the poetic image and the orbits of their formations in the new perception of the concepts of poetry and poetic image. it also looks for sources of figures and how they reflect the general situation, where the poets live, and his expression especially on the psychological and emotional situation of the poet, which is compatible with what is expressed by symbols and legends which are commonly used as rich sources to match the current situation with the time of these symbols and legends.
The use of words: the aesthetics of the poetic image in the contemporary Algerian poem.
القصيدة الجزائرية المعاصرة; الصورة الشعرية; الرموز; الأساطير; جماليات التصوير
Keywords: من بلاغة الكلمة إلى بلاغة الصورة: مضمار التشكيل الجمالي للصورة الشعرية في القصيدة الجزائرية الجديدة.